CONTEMPORARY APPROACHES TO ENHANCING CREDIT RISK MANAGEMENT MECHANISMS IN THE BANKING SYSTEM OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
The increasing complexity of banking operations, rapid digital transformation, and growing economic uncertainty have significantly increased the importance of effective credit risk management in modern banking systems. This study examines contemporary approaches to enhancing credit risk management mechanisms in the banking system of Uzbekistan. The research analyzes existing credit risk management practices, identifies key challenges affecting the quality of risk assessment, and evaluates international experiences related to Basel III standards, IFRS 9 requirements, artificial intelligence, machine learning, and early warning systems. The study employs comparative, analytical, and statistical methods to assess current trends in credit risk management and banking sector stability. Based on the findings, practical recommendations are proposed to improve credit risk assessment procedures, strengthen risk monitoring systems, and increase the resilience of commercial banks. The results indicate that the integration of advanced digital technologies and international risk management standards can significantly enhance the effectiveness of credit risk management and contribute to the sustainable development of Uzbekistan’s banking sector.